Proposta de reator em batelada como alternativa descentralizada para tratamento de esgotos sanitários da área urbana do município de Capitão Leônidas Marques/PR - Paffrath, Silvia Fernanda (2018)
According to indices of sanitary sewage collection in Brazil, until 2016 40% of the population was not served with this type of sanitation service. In municipalities with a predominance of population in the rural area, and/ or with topography unfavorable to exclusively gravity flow, the centralized systems, usually adopted as solution, become economically unviable, since it would require high investments in effluent collection and pumping for routing to the treatment plant. In this sense, the decentralized system become an interesting alternative, with adequate removal of pollutants and for final disposal of domestic sewage. Therefore, the objective of this research was to propose a decentralized alternative for sanitary sewage to the urban area of the municipality of Capitão Leônidas Marques/PR, with the following steps: evaluation of the quality of the sewage generated in the study area, identification of the sites for decentralized sewage treatment units, design of these units, estimation of implementation and maintenance costs, and comparison with the existing centralized project of the Sanitation Company of Paraná (Sanepar). In the characterization of the sewage system, due to the impossibility of obtaining local data, data from the city of Três Barras do Paraná were used in relation to BOD and COD, due to the similarity between municipalities. The suggested treatment method was the sequencing batch reactor (SBR), because of the good percentage of pollutant removals mentioned in the literature and because it is a compact form of activated sludge, treatment proposed by the sanitation company. The sizing of these units followed the classical equation presented in the bibliography. In the estimation of costs were used bibliographic values, preferably of researches with elaboration of budgets. For some items, unit values of the existing Sanepar project were used, such as for sludge drying and expropriation of the areas, for a better comparison between alternatives. In the case of SBR, a supplier proposal was requested. For the final population of 15 thousand inhabitants, the total cost of implementing the decentralized treatment resulted in R$ 652.45 per inhabitant (approximately R$ 9.8 million), about 70% higher than the per capita implantation cost of the sanitation project designed by Sanepar. The complete decentralized system, with collection, resulted in R$ 944.59/inhabitant (approximately R$ 14.2 million), this time 32% smaller than the system designed by Sanepar, with collection network and sewage elevation stations. Thus, from the economic point of view, decentralization proves to be a viable solution for sites without sanitary sewage service.